Gender differences in publication rates in oncology: Looking at the past, present, and future. Issue 12 (25th March 2020) - Duma, Narjust
Abstract : Female physicians and scientists represent less than one third of first and senior authors in oncology journals. Equal opportunities and training in gender bias are necessary to level out the playing field for current and future female physicians and scientists.